2007
DOI: 10.1007/s00421-007-0545-1
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of oxygen uptake efficiency slope based on heart rate reserve end-points in healthy elderly subjects

Abstract: We tested the validity of an new methodological approach to the calculation of oxygen uptake efficiency slope (OUES) [i.e. the use of exercise end-points based on fractions of heart rate reserve (HR(res))], as an alternative to the traditional time-based calculation. Twenty-nine healthy sedentaries >60 years of age (18 males, 11 females) performed an incremental cycling exercise to exhaustion. Respiratory variables and HR were measured breath by breath. Resting and peak variables were calculated and ventilator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 23 publications
(35 reference statements)
3
28
2
Order By: Relevance
“…Among these studies, the OUES has been investigated in healthy adults (n ϭ 7), 4,[24][25][26][27][28][29] in adult patients with a chronic condition (n ϭ 15), 4,8,14,18,21,22,28,[30][31][32][33][34][35][36] and in children (n ϭ 5). 19,21,[37][38][39] The results of aforementioned studies are described below.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these studies, the OUES has been investigated in healthy adults (n ϭ 7), 4,[24][25][26][27][28][29] in adult patients with a chronic condition (n ϭ 15), 4,8,14,18,21,22,28,[30][31][32][33][34][35][36] and in children (n ϭ 5). 19,21,[37][38][39] The results of aforementioned studies are described below.…”
Section: Resultsmentioning
confidence: 99%
“…4,27,29 One study 28 even demonstrated that OUES values calculated from the first half of exercise did not significantly differ from values calculated from the second half or the entire exercise test data. However, another study reported significantly higher values of OUES calculated from data up to 75% and 85% of maximal running speed than those obtained from the entire test data.…”
Section: Influence Of Exercise Duration and Intensitymentioning
confidence: 98%
See 1 more Smart Citation
“…With exercise, the requirement for ventilation increases with oxygen uptake and in patients with cardiorespiratory disease, greater ventilatory effort is required as oxygen uptake rises; this is manifest as a decrease in the oxygen uptake efficiency slope. In addition to not requiring maximal effort, the determination of the oxygen uptake efficiency slope from the respiratory data requires no subjective interpretation of the exercise data [7,15], in contrast to the anaerobic threshold, which may be difficult to identify [16,17] and is subject to observer error [18].…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to note that the OUES determination is not influenced by some intervenient factors, such as the use of experienced and nonexperienced evaluators or test protocol [12]. Moreover, the OUES measurement can be performed without necessarily require a maximal effort or additional experimental sessions [16].…”
Section: Introductionmentioning
confidence: 99%